Double whammy: Congenital glaucoma in phakomatosis pigmentovascularis with Sturge–Weber syndrome and nevus of Ota - S Podury (TNOA Journal of Ophthalmic Science and Research, 2020)
Phakomatosis pigmentovascularis (PPV) is a rare congenital condition characterized by a combination of cutaneous capillary hemangiomas and dermal melanocytosis. The dual presentation of Sturge–Weber syndrome (SWS) and nevus of Ota in the same patient is a rare finding. Individually, both these conditions can predispose to developmental glaucoma. The combined presentation of these two predisposing conditions has a very high chance of coexisting glaucoma. We report a patient of PPV presenting with bilateral SWS, nevus of Ota, and congenital glaucoma.